Conceptualizing friendship in time and place - Risseeuw, Carla. (Value Inquiry Book Series, 2017)
The concept of friendship is more easily valued than it is described: this volume brings together reflections on its meaning and practice in a variety of social and cultural settings in history and in the present time, focusing on Asia and the Western, Euro-American world. The extension of the group in which friendship is recognized, and degrees of intimacy (whether or not involving an erotic dimension) and genuine appreciation may vary widely. Friendship may simply include kinship bonds-solidarity being one of its more general characteristics. In various contexts of travelling, migration, and a dearth of offspring, friendship may take over roles of kinship, also in terms of care.